2005
DOI: 10.1590/s0103-50532005000300018
|View full text |Cite
|
Sign up to set email alerts
|

New pyrone and quinoline alkaloid from Almeidea rubra and their trypanocidal activity

Abstract: O estudo da fração acetato de etila do extrato metanólico das folhas de Almeidea rubra A. St.-Hil. (Rutaceae) permitiu o isolamento de duas substâncias inéditas: 4-metoxi-6-[2-(metilamino)fenil]-2H-piran-2-ona e acetato de rel-(7R,8R)-8-[(E)-3-hidroxi-3-metil-1-butenil]-4,8-dimetoxi-5,6,7,8-tetraidrofuro[2,3-b]quinolin-7-ila; e dos alcalóides arborinina, N-metil-1-hidroxi-3-metoxiacridona, esquimianina, cocusagina, isodutaduprina, isoesquimianina e isococusagina. Através da análise dos dados espectroscópicos f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 12 publications
1
11
0
2
Order By: Relevance
“…Similar studies involving the trypanocidal activity of Meliaceae and Rutaceae species have been reported by our group (Mafezoli et al, 2000;Vieira et al, 2001;Ambrozin et al, 2004Ambrozin et al, , 2005aAmbrozin et al, , 2008 showing that these plants can be considered a promising source of active compounds against trypomastigote forms of T. cruzi. Thus, the significant results obtained from the extracts of C. fruticosa are consistent with those previously reported for this family.…”
Section: Resultssupporting
confidence: 87%
“…Similar studies involving the trypanocidal activity of Meliaceae and Rutaceae species have been reported by our group (Mafezoli et al, 2000;Vieira et al, 2001;Ambrozin et al, 2004Ambrozin et al, , 2005aAmbrozin et al, , 2008 showing that these plants can be considered a promising source of active compounds against trypomastigote forms of T. cruzi. Thus, the significant results obtained from the extracts of C. fruticosa are consistent with those previously reported for this family.…”
Section: Resultssupporting
confidence: 87%
“…This finding indicates that a methoxy group at C-7 is important for AChE inhibition. It has been reported that skimmianine (1), a furoquinoline alkaloid which is abundant in the Rutaceae, has various pharmacological activities such as antiviral and antifungal activities , trypanocidal activity (Ambrozin et al, 2005), antiplatelet aggregation activity (Chen et al, 2000), spontaneous motor activity (Cheng, 1986), cytotoxic activity (Chaturvedula et al, 2003). In this study, we first demonstrated that the total alkaloidal extract from the root of Z. nitidum possessed potent AChE inhibitory activity and skimmianine (1) was responsible compound for this activity.…”
Section: Resultsmentioning
confidence: 65%
“…Kokusaginine ( 37 ) (IC 50 0.560 mM), 34 (IC 50 1.46 mM), and rel ‐(7 R ,8 R )‐8‐[( E )‐3‐hydroxy‐3‐methyl‐1‐butenyl]‐4,8‐dimethoxy‐5,6,7,8‐tetrahydrofuro [2,3‐ b ]quinolin‐7‐yl acetate ( 140 ) (Fig. ) (IC 50 0.977 mM) from Almeidea rubra exhibited moderate in vitro trypanocidal activity against the trypomastigote forms of T. cruzi . Dictamnine ( 40 ) and evolitrine ( 36 , 8‐methoxydictamnine) exhibited antifeedant activity against fourth instar larvae of the tobacco caterpillar Spodoptera litura .…”
Section: Bioactivities Of Quinoline and Quinazoline Alkaloidsmentioning
confidence: 99%